Providing Dual Awareness using Multimodal Cues for Collaborative Manipulation in Virtual Environments - Hyunju Kim; Jung-Min Park (Lawrence Erlbaum Associates Inc., 2024)
Virtual reality (VR) collaborative manipulation requires a proper understanding of the user’s self, other collaborators, and shared objects in the virtual environment. Users must be aware of the movements of themselves and others to coordinate their actions when they hand over an object or move it together. The awareness of collaboration plays an essential role in virtual environments. However, previous studies have focused on providing awareness only for cooperative manipulation. This study proposes a novel framework for dual awareness that comprehensively manages the state of interactions between multiple users and shared virtual objects and provides distinct sensory cues to distinguish themselves from collaborators. The experimental results showed that participants could easily and quickly collaborate on manipulation using our feedback, and they also answered positively in the subjective evaluation.